Vietnam Development Report 2005 : Governance - World Bank (Washington, DC, 2013)
Fundamental changes are taking place in the way the Government of Vietnam operates: the 2001 Constitution empowered the National Assembly to hold votes of no-confidence in the leaders it elects, including ministers. The State Budget Law, effective in January 2004, further expanded those powers, by making the National Assembly responsible for the approval of the budget, including allocations to lower levels of government. In parallel, there is a steady increase in the extent of decentralization. And some successes can be reported in the public administration reform agenda too, in particular, the adoption of the One-Stop Shop (OSS) model at the national level should improve the delivery of administrative services to households and enterprises, and reduce the opportunities for petty corruption. Notwithstanding, it should be recognized that important challenges remain. The goal of this report is to review the progress accomplished so far in building modern governance, and to identify areas where more needs to be done. To attain this goal, the report combines a range of perspectives, and relies on a variety of analytical tools. It carefully reviews patterns in government spending, and revenue at aggregate levels, but also in specific sectors and programs. It evaluates the decision-making processes behind employment and pay policies, investment projects, resettlement programs and budget allocations. It more broadly assesses the justification for government interventions in different aspects of the economy, and the impact of such interventions on key development outcomes, including poverty reduction. Vietnam's continued commitment to inclusive development provides the vision responsive to running an efficient government. Securing rapid economic growth, sustaining continued poverty reduction, and attaining the Vietnam Development Goals, are part of such vision. With this vision in mind, the report flags several areas of concern: planning versus budgeting, and modernizing that planning; better service delivery; redistributing to the poorest; setting budget allocation norms; delegation to spending units; and, management of state assets.